TRANSMISI HABITUS RELIGIUS DI DALAM KELUARGA KATOLIK: ANALISIS INTERAKSIONISME SIMBOLIK ATAS PEMBENTUKAN KEPRIBADIAN ANAK - Ignasius Refo (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2025)
Catholic families hold a central role in transmitting religious values to children from an early age. Amid the growing challenges of modernization, secularization, and digital disruption, this role has become increasingly complex and urgently requires scholarly attention. This article aims to analyse how religious habitus is transmitted within Catholic families and how this process influences the development of children's personalities. The study employs a qualitative approach using a case study method involving Catholic families in various parishes across Ambon. Herbert Mead’s theory of symbolic interactionism serves as the analytical lens to examine the symbolic dynamics within the family—through language, actions, prayer, and Catholic religious symbols—that shape the child's self and religious identity. The findings indicate that the transmission of religious habitus occurs through intense relationships between parents and children, expressed in shared prayer, faith-based discussions, parental role modelling, and participation in ecclesial activities. This process contributes to the development of a religious, empathetic, and resilient personality in children. The study underscores the significance of the family as the primary social space for constructing religious identity and affirms that religious habitus is not merely a legacy of inherited values but a socially enacted practice that is continuously renewed in response to the changing context of the times